A History of Low Birth Weight And The Incident of Stunting In Children Under Five - Nabila, Salwa Shofiya; Siwi, Ignasia Nila (Universitas Respati Yogyakarta, 2025)
The leading cause of infant mortality in Indonesia was low birth weight at 28.2% in 2022. Children under five years old with a history of low birth weight have a higher risk of experiencing growth delays and non-communicable diseases as adults. This research contributed to determining the relationship between a history of low birth weight and the incidence of stunting in children under five. The research design used a case-control with a retrospective approach using maternal and child health books. The sampling technique in this research was simple random sampling. Samples were taken from 238 children under five years old in Wonosari, Special Region of Yogyakarta, Indonesia. Data analysis used the Somers test which showed that there was a relationship between a history of low birth weight and the incidence of stunting in children under five with p = 0.000, the direction of the relationship was positive, and the strength of the relationship was strong, a score of r = 0.560. The OR = 17.907, which means that children under five years old with a history of low birth weight have a 17.907 times risk of experiencing stunting. Children under five years with low birth weight are at greater risk of stunting than children under five years with normal birth weight.